Digital entrepreneurship landscapes in developing Asia: Insights from the Global Index of Digital Entrepreneurship Systems - Erkko Autio; Yothin Jinjarak; Éva Komlósi; Donghyun Park; László Szerb; Mónika Galambosné Tiszberger (Asian Development Bank (ADB), 2024)
Digitalization transforms how entrepreneurs pursue opportunities. To understand this transformative impact on entrepreneurship, we present the Global Index of Digital Entrepreneurship Systems (GIDES), a composite indicator developed to assess the performance of the digital entrepreneurial ecosystem at the national level. To address existing conceptual gaps, GIDES concurrently monitors the general, structural and digital framework contexts supporting digital entrepreneurship. The digital framework conditions, describing the general level of digitalization of the economy, affect entrepreneurial activity through their impact on general and systemic framework conditions. Unlike traditional entrepreneurship or most entrepreneurial ecosystem measures, GIDES takes a systemic approach utilizing the Penalty for Bottleneck (PFB) algorithm to spot bottlenecks connecting elements that could potentially degrade overall system performance. With GIDES, we provide a measure of the digital transformation of entrepreneurship for policymakers who want to improve the quality and productivity potential of the entrepreneurial resource allocation dynamic in their countries. For illustration, GIDES profiles the digital entrepreneurship systems of 113 countries, with a special focus on 21 in developing Asia.
Keywords: L26; O32; O33; O57; 330; entrepreneurship; digitalization; digital entrepreneurship ecosystem; composite indicator; GIDES; Asian developing countries